APPLYING SPATIAL ANALYSIS TO ASSESS SOIL EROSION FOR FOREST PLANTATION AT HONG LINH TOWN, HA TINH PROVINCE - Thi Thuy Linh, Phan; Manh Hung, Bui; Xuan Dung, Bui (Journal of Forestry Science and Technology, 2019)
This study has assessed soil erosion in some protection plantation models at Hong Linh town, Ha Tinh province by applying soil loss prediction equation and spatial analysis. We conducted 20 plots & 80 random points to collect data. To assess soil erosion, the study was based on IDW interpolation in ArcGIS to conduct maps. The results show that (1) There are five main forest types (Pine, mixed Pine and Acacia, Acacia, Eucalypt, mixed Eucalypt & Acacia) in which Pine (Pinus merkusii) is a native species and dominant in protection plantations with 47.65% (665.96 ha); (2) Potential erosion in this study is not high, from 0 - 3.75 and the erosion rate is highest in other forests. Pine forests is from 1.57 to 3.75, vegetation cover is from 0.9 to 1.53, that means C1 coefficient map of each forest type is not much different; (3) Current erosion based on TCVN 2009 are classified into 5 levels in which almost area is eroded slightly and medium. Assessing amount of current erosion based on standard of Hundson (1971), there are 364.74 hectares in the protection plantation are exceed erosion threshold (> 0.8 mm/year) occupied 26.22% in which erosion area of other forest is highest. (4) Keep ground cover and planting replaced species are one of the best solutions to reduce erosion in the protection plantation at Hong Linh.